Tracing nitrate sources with dual isotopes and long term monitoring of nitrogen species in the Yellow River, China - Fu-Jun Yue (Nature Portfolio, 2017)
Abstract A heavy load of nitrogenous compounds reflects nutrient loss and influences water quality in large rivers. Nitrogenous concentrations and dual isotopes of nitrate were measured to ascertain the spatial and temporal distributions of nitrate transformation in the Yellow River, the second-longest river in China. Assessment of the long-term record indicates that [NO3 −–N] has increased by two-fold over the past three decades. Weekly observation of ammonium over a twelve-year period revealed high concentrations and suggests impairment of water quality, particularly since 2011. The estimated total dissolved nitrogen flux was 7.2 times higher in middle reaches than that at head waters. Anthropogenic nitrogen sources become more important in lower section of the upper reaches and middle reaches because of intensive agricultural activities and urban input. Nitrate in the lower reaches was mainly derived from transportation of upstream nitrate and point sources from cities. The spatial variation of ammonium and nitrate isotopes show that nitrification is a key process governing nitrogen transformation. Riverine biological processes could potentially be responsible for the shift of nitrate isotope signature. The first step to reducing nitrogen load and improving water quality will be containment and careful management of sources from urban input, sewage waste and irrigation runoff.